2014
DOI: 10.1017/s0007114514001214
|View full text |Cite
|
Sign up to set email alerts
|

Short-term obesity results in detrimental metabolic and cardiovascular changes that may not be reversed with weight loss in an obese dog model

Abstract: The time course of metabolic and cardiovascular changes with weight gain and subsequent weight loss has not been elucidated. The goal of the present study was to determine how weight gain, weight loss and altered body fat distribution affected metabolic and cardiovascular changes in an obese dog model. Testing was performed when the dogs were lean (scores 4 -5 on a nine-point scale), after ad libitum feeding for 12 and 32 weeks to promote obesity (.5 score), and after weight loss. Measurements included serum g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 67 publications
(67 reference statements)
7
38
0
3
Order By: Relevance
“…The HOMA insulin resistance scores were also lowest when the dogs were on this feeding regime, which is a reflection of both low fasting glucose and insulin concentrations. Both caloric restriction and a reduction in fat mass improves insulin sensitivity in overweight dogs (83)(84)(85)(86). In our study, intermittently fasted dogs eating a HF diet lost less weight than when intermittently fasted on a LF diet, and yet had lower insulin concentrations.…”
Section: Discussionsupporting
confidence: 44%
“…The HOMA insulin resistance scores were also lowest when the dogs were on this feeding regime, which is a reflection of both low fasting glucose and insulin concentrations. Both caloric restriction and a reduction in fat mass improves insulin sensitivity in overweight dogs (83)(84)(85)(86). In our study, intermittently fasted dogs eating a HF diet lost less weight than when intermittently fasted on a LF diet, and yet had lower insulin concentrations.…”
Section: Discussionsupporting
confidence: 44%
“…The effects of feeding the pea and rice diets for 12 weeks in obese beagles on body fat, leptin and adiponectin, and cardiovascular parameters are shown in Table . Diet did not result in any significant improvements in cardiovascular parameters even though this laboratory has previously shown that heart rate and systolic left ventricular free wall thickness were increased when dogs became obese compared to when they were normal weight (Adolphe et al., ). Similarly, total, visceral and subcutaneous body fat measured by CT did not differ between diets.…”
Section: Resultsmentioning
confidence: 82%
“…20 We are not aware of a similar study in dogs, although 1 investigation using computed tomography showed equal increments of visceral and subcutaneous adipose tissue in dogs during weight gain. 89 …”
Section: Abdominal Fat Distributionmentioning
confidence: 99%